Closing extra CO2 into plants for simultaneous CO2 fixation, drought stress alleviation and nutrient absorption enhancement. Issue 42 (December 2020) - Liang, Feihong; Yang, Wenjie; Xu, Lang; Ji, Long; He, Qingyao; Wu, Lanlan; Ran, Yi; Yan, Shuiping
Graphical abstract: Highlights: CO2 introduction in form of HCO- 3 enhances the nutrient absorption of lettuce. HCO- 3 utilization protects the carbon assimilation of lettuce at drought stress. CO2 in form of HCO- 3 is mainly fixed by the epidermal photosynthesis of lettuce. Abstract: The technical feasibility of bio-fixation of extra CO2 into plants was investigated in this study using biogas slurry as CO2 carrier and lettuce as the model plant. CO2 was absorbed into 5-times-concentrated-biogas-slurry (5-CBS) to act as the hydroponic solution for lettuce cultivation while chemical nutrient solution was tested as a control. Effects of these solutions on lettuce cultivation performance such as lettuce growth and nutrient absorption were compared. Also, mechanisms of CO2 bio-fixation from biogas slurry into the lettuce was explored by exposing lettuces to different drought stress. Results showed that CO2 -rich 5-CBS can cultivate the lettuce for achieving similar growth performance (main-root length, plant height, stem diameter and biomass) to the chemical nutrient solution, confirming its low phytotoxicity to lettuce. CO2 introduction in form of HCO3 − into biogas slurry can enhance N, P and K absorption performance of the lettuce, which is 42.53 %, 167.87 % and 18.03 % higher than that of chemical nutrient solution, respectively. Furthermore, CO2 in form of HCO3 − from the hydroponic solution was mainly fixed into the lettuce stem through being involved in the lettuce epidermal photosynthesis. HCO3 − can be decomposed to generate water for compensating the internal water deficient environment and CO2 for protecting the photosynthetic system of lettuce from injury caused by the drought stress. Due to the utilization of HCO3 −, the whole carbon utilization rate of lettuce can be maintained about 14.13 μmol−HCO3 − /(m 2 ·s) under the drought stress, which is higher than the photosynthetic rate for the case without the drought stress.